Relationships among self-study ability, critical thinking ability, cooperative ability, and problem-solving ability in Chinese undergraduate nursing students: an analysis of a longitudinal cohort via cross-lagged models - Liu, Dun; Lin, Jianbin; Zhang, Jincheng; Luo, Xinchu (Frontiers in Psychology, 2025)
BackgroundThere is currently a lack of research on the change in self-study ability, critical thinking ability, collaborative ability, and problem-solving ability in undergraduate nursing students before and after completing professional courses with blending teaching, as well as the mutual influence of different abilities.ObjectiveTo understand the longitudinal and bidirectional relationships among self-study ability, critical thinking ability, collaborative ability, and problem-solving ability in undergraduate nursing students.MethodA longitudinal study design was implemented, incorporating two distinct temporal measurement points: baseline assessment prior to the commencement of professional nursing courses and subsequent evaluation following course completion. Correlation analysis and a cross-lagged model were used to explore the changes in various abilities of undergraduate nursing students before and after completing professional courses, as well as the interactions between different abilities.ResultProblem-solving skills were correlated with various other variables. Self-directed learning ability at the initial time point was negatively correlated with certain variables. Self-study ability had a significant and negative predictive effect from Time 1 to Time 2. Collaborative ability significantly and positively influenced self-study ability from Time 1 to Time 2. Problem-solving ability showed a significant and positive predictive effect from Time 1 to Time 2 and positively influenced collaborative ability from Time 1 to Time 2. Self-study ability had a significant and negative impact on critical thinking from Time 1 to Time 2.ConclusionUndergraduate Nursing students' self-study, collaborative, and problem-solving abilities are interrelated. Beginning in the early years of study, educators should revamp teaching methods and models to assist students in unlearning conventional learning and thought processes. Teachers should aim to foster collaborative problem-solving skills by applying knowledge, thereby augmenting students' overall problem-solving proficiency.